STUDENTS’ EXPERIENCES OF USING DEEPL IN EFL WRITING CLASSROOMS: A SYSTEMATIC LITERATURE REVIEW - Payungallo, Aubreylia Visca (JEELL (Journal of English Education, Linguistics and Literature), 2026)
In education, Artificial Intelligence (AI) technologies significantly assist students in their language learning. One of the technologies is DeepL. Thus, it is essential to identify the factors shaping students’ positive experiences, as well as the challenges they face, while utilizing DeepL, specifically for their English writing activities. To complete the study’s goal, the writer used the Google Scholar database to explore fifteen peer-reviewed journal articles published between 2020 until 2025. The findings of this study could be divided into five themes: (1) DeepL gives accurate translation results, (2) DeepL improves users’ ability in writing, (3) DeepL offers various alternative words or synonyms, (4) DeepL causes students over reliance on the tool, and (5) DeepL struggles with translating specialized items. Each theme’s discussions provide information about relevant studies, offer practical suggestions (e.g. expanding the scope of literature review by incorporating a wider range of academic databases and source types) to address the limitations, and suggest future research directions (e.g. investigating the long-term effects of DeepL on students’ writing skills and methods teachers can employ to reduce students’ dependency on the tool).